Pakistan - Towards an Integrated National Safety Net System : Assisting Poor and Vulnerable Households, An Analysis of Pakistan's Main Cash Transfer Program - World Bank (Washington, DC, 2013)
The vision of Pakistan's social protection strategy to reach the poor and vulnerable (2007) is 'to develop an integrated and comprehensive social protection system, covering all the population, but especially the poorest and the most vulnerable'. Consistent with this vision, the goals of the strategy are identified as: 1) to support chronically poor households and protect them against destitution, food insecurity, exploitation and social exclusion; 2) to protect poor and vulnerable households from the impacts of adverse shocks to their consumption and well-being that, if not mitigated, would push non poor households into poverty, and poor households into deeper poverty; and 3) to promote investment in human and physical assets, including health, nutrition, and education, by poor households capable of ensuring their resilience in the medium run and of interrupting the intergenerational cycle of poverty. This vision is fully consistent with the World Bank's social protection and labor strategy for 2012-2022, which recognizes that effective social protection and labor policies and programs help create the resilience, equity and access to jobs and opportunities essential to save lives, reduce poverty and promote sustainable growth. The focus of this report is Pakistan's main safety net program: the Benazir Income Support Program (BISP), which is only one part of the broader poverty reduction and social protection interventions. In particular, social protection includes labor policy, contributory social insurance, and social care services as well as safety nets. Pakistan's social protection system comprises safety nets, social security and employment promotion and protection.